Alpha5 Nicotinic Acetylcholine Receptor Contributes to Nicotine-Induced Lung Cancer Development and Progression - Sun, Hai-Ji; Jia, Yan-Fei; Ma, Xiao-Li (Frontiers in Pharmacology, 2017)
Nicotine and nicotinic acetylcholine receptors (nAChRs) are considered to be involved in lung cancer risk, onset and progression, but their precise physiological roles in these contexts remain unclear. Our previous studies suggested that α5-nAChR mediates nicotine-induced lung cancer cell proliferation, migration and invasion in vitro. In this study, we aimed to determine the role of α5-nAChR in the development and progression of non-small cell lung cancer (NSCLC). Our microarray results reveal that knockdown of the CHRNA5 gene encoding α5-nAChR significantly modulates key pathways including the cell cycle, DNA replication, pathway in cancer. α5-nAChR knockdown in cultured A549 cells affected cell cycle distribution, apoptosis, and cyclin expression. In vivo, α5-nAChR silencing inhibited the growth of lung tumors, especially in the context of nicotine exposure. Importantly, α5-nAChR expression in patient tumors correlated with the primary T stage, N stage and reduced survival time. These results reveal that α5-nAChR silencing inhibits the progression of nicotine-related NSCLC, making this receptor a potential pharmacological target for the treatment of nicotine-related lung carcinogenesis.